Comparing Functions: A Fundamental Approach in Mathematical Analysis - Мaksetova Zuhra Kabulovna (Euro Asian Journal Publishing, 2024)
A comparison of functions is an analytical approach used to identify and contrast the characteristics of two or more mathematical functions. This comparison focuses on several key aspects. cComparing functions is a fundamental technique in mathematics, enabling a deeper understanding of their properties, relationships, and applications
Keywords: Domain; Range; Intercepts; Slope